The STop UNhealthy substance use now (STUN II) trial: protocol for a 48-site cluster randomized 2 × 2 factorial implementation trial to improve evidence-based screening and interventions for substance use disorder within primary care - Jonas, Daniel E.; Brill, Seuli Bose; Fried, Martin; Brouwer, Leslie; Riley, Sean; MacEwan, Sarah R.; Hyer, Madison; Palettas, Marilly; Hall, Orman Trent; Vilensky, Michael; Teater, Julie; Carson, William Felkel; et al. (Implementation science : IS, 2025)
Background Despite substance use disorders (SUD) being a leading cause of preventable death in the US, most people who visit primary care in the US are not screened for SUD. There are multiple barriers to screening for, identifying, and managing SUD in primary care. However, there are also promising strategies available to address these barriers, including practice facilitation (PF), learning collaboratives (LC), and performance incentives (PI). Methods This study is a 48-site cluster-randomized 2 × 2 factorial implementation trial that aims to compare the effectiveness of several strategies for implementing evidence-based screening and interventions for SUDs in primary care. Practices will be randomized to one of four implementation strategies: (1) PF only, (2) PF + LC, (3) PF + PI, or (4) all three strategies. An estimated 144 participants from 48 primary care practices will be enrolled. All participants will receive PF to guide them in making changes to implement screening for SUD, focusing on a defined change package and associated tools. PF includes quality improvement (QI) coaching, as well as electronic health record (EHR) support, training, and expert consultation. LC includes monthly virtual education sessions led by content experts to support practice improvement and innovation with didactics on key topics as well as facilitating participant interactions to share experiences. PI includes financial incentives for performance. Primary care practices will be the unit of analysis for both the primary outcome (rate of SUD screening) and secondary outcomes (rates of evidence-based interventions for SUD). Assessments will be conducted during a 12-month implementation phase and 12-month sustainment phase. Discussion This study will produce evidence regarding the comparative effectiveness of several strategies on implementation and sustainment of evidence-based screening and interventions for SUD within primary care. It will also generate knowledge about mechanisms of change in primary care settings. The results are expected to have a positive impact by providing a nuanced understanding of the incremental benefits of LC and/or PI to inform primary care practices, health systems, policymakers, and payers about optimal implementation strategies for SUD screening and evidence-based interventions. Trial registration ClinicalTrials.gov NCT06524232. July 23, 2024 –registered.